CONSTRUCTING AND PRESERVING ETHNIC IDENTITY THROUGH CULTURAL PRACTICES AMONG THE REJANG COMMUNITY IN CENTRAL BENGKULU - susiyanto, susiyanto; Khairani, Eni; Safitra, Linda (Universitas Padjadjaran, 2025)
Bengkulu Province is characterized by rich ethnic and cultural diversity, with the Rejang ethnic group as the majority population. Amid ongoing social change and modernization, the Rejang community continues to maintain its ethnic identity through various cultural practices. This study aims to analyze the processes through which ethnic identity is constructed and preserved within the Rejang community in Central Bengkulu. Using a qualitative research design with an ethnographic approach, the study was conducted in Pondok Kelapa and Talang Empat sub-districts, areas with a strong presence of Rejang communities. Data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive data analysis model. The findings show that Rejang ethnic identity is constructed and sustained through key cultural symbols and practices, including the use of the Rejang language, a patrilineal kinship system, the Ka-Ga-Ma script, and traditional ceremonies such as Bekejai (marriage) and Ngamban Tanduk (birth and naming rituals). Although several cultural practices have adapted to religious influences and contemporary social conditions, their core values and meanings remain preserved. This preservation is supported by the active roles of families, customary institutions, and community leaders in transmitting cultural values across generations. This study demonstrates that ethnic identity is a dynamic social process shaped by continuous interaction and adaptation. The findings contribute to sociological discussions on ethnic identity and offer practical insights for stakeholders in supporting the sustainability of local cultures amid social change.